Probable case of autosomal dominant myotonia congenita (Thomsen disease) seen in Sokoto, Nigeria - Isezuo, Khadijat O.; Sani, Usman M.; Garba, Bilkisu I.; Waziri, Usman M.; Ahmad, Murtala M.; Ahmed, Hadiza K.; Inoh, Ikemesit I.; Okwuolise, Olubusola B.; Jangebe, Mikailu A.; Alimi, Saeed (International Journal of Contemporary Pediatrics, 2024)
Myotonia congenita is a rare heritable disease of skeletal muscles characterized by muscle stiffness (myotonia) and hypertrophy. We report a child with features of autosomal dominant type of myotonia congenita seen at our hospital. A 4-year-old boy admitted for an acute febrile illness was observed to have generalized muscular hypertrophy said to be present since he was 7 months old. It was associated with painless generalized muscle stiffness and slow initiation of movements after period of rest which gradually subsided following a few minutes of activity. He also had history of frequent falls while running, but no difficulty climbing stairs or muscle weakness. Pregnancy and delivery were uneventful. He had normal developmental milestones and was doing well in school. No history of similar problem in any family member and his parents were not consanguineous. On examination he had generalized muscular hypertrophy with a Herculean build. He had demonstrable stiff movements and gait after rest with percussion myotonia. Gower sign was negative. Serum creatinine kinase was normal at 79.2 U/L (Up to 130 U/L) and CK-MB was 24.8 U/L (Up to 24 U/l)). Electromyography (EMG) showed myotonia as sharp waves in a waxing and waning pattern. Muscle biopsy and genetic test were not done due to non-availability. A diagnosis of myotonia congenita most likely autosomal dominant type (Thomsen disease) was made based on strongly suggestive clinical features and EMG in the patient. He was since discharged as acute febrile illness resolved but still has symptoms of myotonia. This is the first reported case of myotonia congenita in our environment supported by clinical and EMG features. Genetic diagnosis should be made available in resource limited settings.